Smart Safety Monitoring System for Sewage Worker - Vaibhav Jadhav; Sakshi Jadhav; Dnyaneshwari Gardare; Dr. Sudhir Divekar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents a comprehensive smart moni- toring system designed to enhance the safety of sewage workers. The sewage monitoring system integrates multiple sensors to detect hazardous gases such as carbon monoxide, hydrogen sulfide, and methane that pose significant health risks to workers. The system utilizes a heartbeat sensor to monitor the pulse rate of workers in real-time, providing immediate alerts when abnormal health indicators are detected. By incorporating IoT capabilities, the system offers remote monitoring and two-way communication, enabling quick response during emergencies. The proposed system addresses critical safety concerns in sewage maintenance operations, where workers frequently face life- threatening environments due to toxic gas exposure and con- fined spaces. Experimental results demonstrate the system’s effectiveness in detecting dangerous gas levels and monitoring workers’ vital signs with reliable communication in underground environments using LoRa technology.
Keywords: Sewage monitoring; IoT; gas sensors; worker safety; LoRa communication; real-time monitoring; heart rate sensing